Enhancing the Science Performance of Grade 11 HUMSS Students Through Writing-Based Activities - Rainiel Bryan Domasian (Education Policy and Development, 2025)
Writing activities, including research paper writing, learning logs, lab reports, and essays, were systematically incorporated into the curriculum to enhance students' learning experiences. This study examined the impact of integrating writing-based activities into science instruction, focusing on 35 Grade 11 HUMSS students. Utilizing a pre-test/post-test experimental design, the research was conducted over three weeks and encompassed two science lessons to assess the effectiveness of this approach. Pre-test and post-test assessments, as well as teaching materials, were used as research instruments. The findings revealed a significant improvement in post-test scores (Mean = 21.68, SD = 2.45) compared to pre-test scores (Mean = 12.57, SD = 2.29), with a p-value of 2.60E-18, demonstrating the effectiveness of these activities. This outcome highlights the potential of writing-based activities to enhance science performance and advocates for their broader implementation across subjects and grade levels. Furthermore, it underscores the importance of providing professional development for teachers and establishing a monitoring system to sustain the positive impact of these activities on student academic achievement.